In Situ Forming, Enzyme-Responsive Peptoid-Peptide Hydrogels: An Advanced Long-Acting Injectable Drug Delivery System - Coulter, Sophie M.; Pentlavalli, Sreekanth; An, Yuming; Vora, Lalitkumar K.; Cross, Emily R.; Moore, Jessica V.; Sun, Han; Schweins, Ralf; McCarthy, Helen O.; Laverty, Garry (Journal of the American Chemical Society, 2024)
Long-acting drug delivery systems are promising platforms to improve patient adherence to medication by delivering drugs over sustained periods and removing the need for patients to comply with oral regimens. This research paper provides a proof-of-concept for the development of a new optimized in situ forming injectable depot based on a tetrabenzylamine-tetraglycine-d-lysine-O-phospho-d-tyrosine peptoid-D-peptide formulation ((NPhe)4GGGGk(AZT)y(p)-OH). The chemical versatility of the peptoid-peptide motif allows low-molecular-weight drugs to be precisely and covalently conjugated. After subcutaneous injection, a hydrogel depot forms from the solubilized peptoid-peptide-drug formulation in response to phosphatase enzymes present within the skin space. This system is able to deliver clinically relevant concentrations of a model drug, the antiretroviral zidovudine (AZT), for 35 days in Sprague–Dawley rats. Oscillatory rheology demonstrated that hydrogel formation began within ∼30 s, an important characteristic of in situ systems for reducing initial drug bursts. Gel formation continued for up to ∼90 min. Small-angle neutron scattering data reveal narrow-radius fibers (∼0.78–1.8 nm) that closely fit formation via a flexible cylinder elliptical model. The inclusion of non-native peptoid monomers and D-variant amino acids confers protease resistance, enabling enhanced biostability to be demonstrated in vitro. Drug release proceeds via hydrolysis of an ester linkage under physiological conditions, releasing the drug in an unmodified form and further reducing the initial drug burst. Subcutaneous administration of (NPhe)4GGGGk(AZT)y(p)-OH to Sprague–Dawley rats resulted in zidovudine blood plasma concentrations within the 90% maximal inhibitory concentration (IC90) range (30–130 ng mL–1) for 35 days.